Pola Komunikasi Interpersonal Orangtua Terhadap Anak dalam Bermain Game Smartphone di SD Negeri Lanbau 02 Citeureup - Winda Ira Amelia (Jurnal Ilmu Komunikasi, 2024)
The purpose of this research is to find out how the pattern of interpersonal communication between parents against children in playing game smartphone at SD Negeri Lanbau 02 Citeureup and what are obstacles do parents experience in communicating with children. The method used in this research is descriptive qualitative. The techniques for collecting data in this research is interview, observation, and documentation. The data analysis techniques used in this research is data reduction, data display and conclusions drawing. The results of this research is indicate that there are two types of parental communication patterns namely authoritarian and authoritative. However, the more dominantly applied is authoritarian communication pattern. The obstacles do parents experience in communicating with children is children are hard to tell, do not want to listen what parents say, when parents say something sometimes children do not understand and limited time that parents and children have because both of them busy so that communication becomes less intense between parents and children.